A case report of the sustained and rapid response of bevacizumab in a TP53-positive breast cancer and liver metastatic patient through personalized medicine - Eskandarion, Mohammad Reza; Tizmaghz, Zahra; Andalib, Bahram; Parsa, Nasser; Emami, Seyed Amir Hossein; Shahsiah, Reza; Oghabian, Mohammad Ali; Shirkoohi, Reza (Frontiers in Oncology, 2022)
HER2-positive metastatic breast cancer is much less frequent than other subgroups of breast cancer. Treatment options for this cancer are mostly limited to systemic chemotherapy, which leads to moderate improvements. Targeted therapy against malignant breast cancer requires the identification of reliable biomarkers for personalized medicine to obtain the maximum benefit of this therapy. Any mutations in the TP53 signaling pathway can be considered a significant causative factor of breast cancer, for which the identification of target genes plays an important role in selecting the appropriate treatment. The use of personalized gene expression profiling could be valuable to find the direct target of the treatment in this case. The present study assessed the genetic profile of a HER2-positive metastatic breast cancer patient (with a liver metastasis) and figured out a complete and sustained response to Bevacizumab. According to the results of Next Generation Sequencing (NGS) analysis, the patient’s genetic profile showed an increased expression of p4EBP1 and PTEN and the activation of the mTOR signaling pathway with a mutation in the TP53 gene. Based on the common treatment of similar profiling, we administrated Bevacizumab / Taxol / Gemzar chemotherapy for up to six courses. Accordingly, as the response to treatment was revealed by reducing the volume of the liver metastasis from 4cm to 1.4cm, metastasectomy was performed as a complementary treatment. Hence, personalized gene expression profiling is not only useful for targeted therapy but could also be recommended to avoid the prescription of non-responsive drugs.